Odpowiedź :
a)
x^(4/7) - 8*x^(2/7) = 0
x^(4/7)=8*x^(2/7)/:√(x^(2/7))
x^(2/7)=8
x=8^(7/2)
b)
³√x -8* ³√(x²) = 0
³√x=8³√(x²) /:√(x²)
³√x=1/8
x=1/512
x^(4/7) - 8*x^(2/7) = 0
x^(4/7)=8*x^(2/7)/:√(x^(2/7))
x^(2/7)=8
x=8^(7/2)
b)
³√x -8* ³√(x²) = 0
³√x=8³√(x²) /:√(x²)
³√x=1/8
x=1/512
a)
x^(4/7) - 8*x^(2/7) = 0
x^(4/7) = 8x^(2/7)
x^(2/7) = 8
x = 8^(7/2)
b)
³√x -8* ³√(x²) = 0
³√x = 8* ³√(x²)
x^(1/3) = 8* x^(2/3)
1 = 8 * ³√x
1/8 = ³√x
x=1/512
x^(4/7) - 8*x^(2/7) = 0
x^(4/7) = 8x^(2/7)
x^(2/7) = 8
x = 8^(7/2)
b)
³√x -8* ³√(x²) = 0
³√x = 8* ³√(x²)
x^(1/3) = 8* x^(2/3)
1 = 8 * ³√x
1/8 = ³√x
x=1/512